Switching antipsychotics: Results of 16-month non-interventional, prospective, observational clinical research of inpatients with schizophrenia spectrum disorders - Bole Cvetka Bačar; Pišlar Mitja; Šen Metka; Tavčar Rok; Mrhar Aleš (Acta Pharmaceutica)
The study aims to identify prescribing and switching patterns of antipsychotics in clinical practice. A 16-month, prospective study was conducted at the Psychiatric Hospital Idrija, Slovenia. Inpatients (N = 311) with schizophrenia spectrum disorders were observed. The causes for switching antipsychotics and switching strategies were analyzed. Analyzing a total of 3954 prescriptions, the collected data confirmed that treatment strategies in this psychiatric hospital are very complex. It was found that 37 percent of inpatients had at least one switch. Moreover, switches that included three or more antipsychotics were detected. The most common causes for switching antipsychotics were adverse reactions and inefficacy or lack of efficacy. Among switching options, abrupt switch was recorded several times. As some patients are receiving several antipsychotics at the same time, it is possible that unusual switching occurs in clinical practice. It seems that the choice of switching strategy is also affected by the cause and urgency for switching an antipsychotic.